2021
DOI: 10.1007/s12144-021-01697-5
|View full text |Cite
|
Sign up to set email alerts
|

How self leadership enhances normative commitment and work performance by engaging people at work?

Abstract: Leadership and its connection with social sustainability are frequently prescribed for effective management. Integrating self-leadership among the employees is an emerging area to focus on empowering an organization. The principal objective of this study was to empirically investigate the impact of self-leadership on normative commitment and work performance through the mediating role of work engagement. This phenomenon of self-leadership was explained by using the theoretical lens of the social cognitive theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…Another study had also found a growing consensus that engagement could mean high levels of energy and job involvement (Bakker 2017). Thus, engagement is often defined as an intellectual and emotional commitment to an organisation (Inam et al 2021) or the amount of voluntary effort exhibited by employees in the workplace. Frank, Finnegan and Taylor (2004) correspondingly described engagement as employees' positive attitudes towards an organisation and its values.…”
Section: Job Engagementmentioning
confidence: 99%
“…Another study had also found a growing consensus that engagement could mean high levels of energy and job involvement (Bakker 2017). Thus, engagement is often defined as an intellectual and emotional commitment to an organisation (Inam et al 2021) or the amount of voluntary effort exhibited by employees in the workplace. Frank, Finnegan and Taylor (2004) correspondingly described engagement as employees' positive attitudes towards an organisation and its values.…”
Section: Job Engagementmentioning
confidence: 99%
“…On the other hand, the literature is limited in terms of theory-driven, empirical studies that examine the interlinking mechanisms between self-leadership and work-role performance. The extant research focused on selfefficacy (Chaijukul, 2010;Panagopoulos and Ogilvie, 2015), job satisfaction (Chaijukul, 2010), and work engagement (Inam et al, 2021) as three mediating mechanisms that link self-leadership into work-role performance. Relying on SDT (Deci et al, 2017) and Zimmerman (1995Zimmerman ( , 2000 empowerment theory, we suggest that psychological empowerment might also serve as an overarching motivational mechanism through which self-leadership behaviors are translated into better work role performance.…”
Section: Self-leadership and Work Role Performancementioning
confidence: 99%
“…Regarding its performance-related outcomes, empirical evidence has shown that self-leadership affects employees' work performance positively (Griffin et al, 2007), enhancing their task proficiency, adaptability, and proactivity (Hauschildt and Konradt, 2012;Marques-Quinteiro and Curral, 2012;Bailey et al, 2018;Marques-Quinteiro et al, 2019). On the other hand, the literature is limited in terms of the theory-driven, empirical studies (e.g., Panagopoulos and Ogilvie, 2015;Inam et al, 2021) that explore the mechanisms through which self-leadership nurtures different aspects of work role performance. Indeed, although previous research has focused on a diverse group of variables (i.e., self-efficacy, work engagement, job satisfaction) that link self-leadership to performance, the motivational, selfempowerment process starting with self-leadership and leading to increased work role performance is under-researched and warrants empirical examination (Goldsby et al, 2021), particularly in remote work settings.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, "fearless" can be associated with behavioral awareness in that individuals position themselves such that they motivate the self to be successful (Schultz, 2021). Secondly, both "not what is easy" and "new" relate to individuals' adaptive ability in leading the self, whilst engaging in naturally motivating tasks (Inam et al, 2021). Thirdly, "question everything" refers to an intolerance of accepting negative experiences as detrimental, whilst asking questions to the self in order to develop self-trust and commitment, and embracing new ideas and opportunities (Campos et al, 2020).…”
Section: The Power Of Self-leadershipmentioning
confidence: 99%